TINJAUAN TERHADAP TINDAK PIDANA MEMILIKI KARTU TANDA PENDUDUK (KTP) GANDA BERDASARKAN UNDANG-UNDANG NO. 24 TAHUN 2013 TENTANG ADMINISTRASI KEPENDUDUKAN - Reza Fahlevi (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
Abstract KTP is a population document that must be owned by every citizen. Population Documents are official documents issued by Implementing Agencies that have legal force as authentic evidence produced from the Population Registration and Civil Registration services.This study uses a type of normative legal research that is a legal research method carried out by examining mere literature or secondary data using the Law and Concept approach.The results of the study stated that the process of law enforcement against the owners of multiple ID cards according to law 24 of 2013 concerning population administration regarding changes to the law no. 23 of 2006 concerning population administration Every resident who intentionally registers as a family head or family member of more than one KK as referred to in Article 62 paragraph (1) or to have more than one KTP as referred to in Article 63 paragraph (6) is convicted of a maximum imprisonment of 2 (two) years and / or a maximum fine of Rp. 25,000,000.00 (twenty-five million rupiah). Efforts made by the Samarinda City Population and Civil Registry Office need to be appreciated, because in order to overcome these problems the agency maximizes the readiness of employees in serving residents with an average time of less than 10 minutes of registration for KTP-el registration can already be included in the data collection. Efforts to elucidate the KTP-el function are carried out on the community starting from PKK, RT, RW, Kelurahan, Kecamatan, and cooperation with other agencies in Samarinda city until cooperation with the Population and Civil Registry Office of Surabaya City is an activity to realize the optimal KTP-el function for the needs of the population Samarinda City.